2020
DOI: 10.1038/s41597-020-00732-7
|View full text |Cite
|
Sign up to set email alerts
|

DISPERSE, a trait database to assess the dispersal potential of European aquatic macroinvertebrates

Abstract: Dispersal is an essential process in population and community dynamics, but is difficult to measure in the field. In freshwater ecosystems, information on biological traits related to organisms’ morphology, life history and behaviour provides useful dispersal proxies, but information remains scattered or unpublished for many taxa. We compiled information on multiple dispersal-related biological traits of European aquatic macroinvertebrates in a unique resource, the DISPERSE database. DISPERSE includes nine dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 58 publications
(75 reference statements)
0
69
1
1
Order By: Relevance
“…This group of organisms is widely used in water quality biomonitoring. Large scale routine surveys have provided huge datasets gathering information on their distribution, community composition and some of their traits (Tachet et al 2010, Schmidt‐Kloiber and Hering 2015, Sarremejane et al 2020). Based on the assumption that macroinvertebrate development follows predictions of GRH originally addressing growth rate, we specifically addressed the questions whether 1) the stoichiometry (N:P, C:P, C:N) of macroinvertebrates can be linked to their development‐related traits and 2) the community composition regarding development characteristics can be related to changes in environmental nutrient concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This group of organisms is widely used in water quality biomonitoring. Large scale routine surveys have provided huge datasets gathering information on their distribution, community composition and some of their traits (Tachet et al 2010, Schmidt‐Kloiber and Hering 2015, Sarremejane et al 2020). Based on the assumption that macroinvertebrate development follows predictions of GRH originally addressing growth rate, we specifically addressed the questions whether 1) the stoichiometry (N:P, C:P, C:N) of macroinvertebrates can be linked to their development‐related traits and 2) the community composition regarding development characteristics can be related to changes in environmental nutrient concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…To classify taxa according to their documented ability to tolerate drying via resistance and/or resilience mechanisms, we used nine traits (subdivided in 23 categories; Table S2) relating to life cycles, morphology, physiology and behaviour, sourced from Tachet et al (2010) and Sarremejane, Cid, et al (2020). We used a fuzzy‐coding approach to assign traits to taxa at the genus level, with affinities standardized as the percentage affinity for each category within a trait.…”
Section: Methodsmentioning
confidence: 99%
“…The general purpose of our study was to test how dispersal ability modifies SOFD distribution in eight macroinvertebrate orders from 14 eutrophic lakes in southern Finland. Previous study has found that different aquatic insect orders differed in dispersal ability (Sarremejane et al 2020).…”
Section: Introductionmentioning
confidence: 96%